THE ROLE OF FAMILY ENVIRONMENT IN PREDICTING ACCULTURATION STRATEGIES - Gharibian, George (Modern Psychology, 2025)
Family environment, particularly family dynamics, plays a crucial role in shaping individuals’ self-concepts, which in turn influence the development of their ethnic identity. Ethnic identity can affect how immigrants perceive both their heritage culture and the host culture. If individuals relate positively to their family, they are more likely to value their family culture, while negative family experiences may result in the rejection of their family culture. These familial experiences can also extend to influence interpersonal relationships outside of the family. A positive identification with one’s own culture is often associated with more positive interactions with other cultures. This study revisits primary archival data on family environment and acculturation, providing a reinterpretation of the results through the lens of an updated literature review. It is hypothesized that the family environment can influence acculturation strategies such that more positive experiences lead to more positive acculturation strategies, and conversely, negative experiences may lead to more negative acculturation experiences. Analysis of the data partially supports these hypotheses, indicating that participants who reported more conflictual experiences with their family tended to reject their family heritage culture and adopt more stressful acculturation strategies, such as the marginalization strategy. However, a positive family environment was not a significant predictor of acculturation strategies. Additionally, age and years residing in the U.S. were examined as control variables. The discussion explores the implications of the findings in the areas of individual and family therapy.